Maneuvering the bumps in the New Silk Road: Open innovation, technological complexity, dominant design, and the international impact of Chinese innovation - Alexander Brem; Petra A. Nylund (R&D Management, 2021)
Chinese innovation is again flowing westwards, which is fomented by China's Belt and Road Initiative. In this context, we study the international impact of innovations from specific countries. Based on panel data of patents from 27 countries over 17~years, we find that levels of open innovation, technological complexity, and dominant design influence the international impact of innovations from a country. Contrary to earlier research, however, this influence is negative when open innovation activities are involved. This is particularly relevant in the context of Chinese innovation, in which the same innovation networks that promote efficient production may hinder the development of innovations. Due to the innate uncertainty and newness of innovation, partners beyond the common local and long-term networks must be included. Hence, to effectively create a New Silk Road of Innovation, innovation ecosystems may need to expand across national borders. This opens up fruitful avenues for future research, and individuals with multiple cultural identities can bridge the gaps between contexts.
Keywords: 650